2012
DOI: 10.2118/136107-pa
|View full text |Cite
|
Sign up to set email alerts
|

Casing While Drilling (CwD): A New Approach To Drilling Fiqa Formation in the Sultanate of Oman—A Success Story

Abstract: Highly reactive Fiqa shale used to compel well engineers in the Sultanate of Oman to plan drilling phase of surface and intermediate sections primarily based on time exposure to aqueous drilling fluid water-based mud (WBM). The new approach of drilling the time-dependent Fiqa formation using casing-while-drilling (CwD) allows well engineers to plan prospective top/intermediate wellbore sections differently by enhancing the overall drilling performance. This reduces the risk of setting casing strings at unplann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Several examples from applications around the world include Canadian arctic permafrost by Vrielink et al (2008), Lobo field in south Texas by Fontenot (2003), in Brazil by Placido et al (2005 and, Mississippi Canyon by Rosenberg and Gala (2012), in Peruvian Jungle by Beaumont et al (2010), in Saudi Arabia by Chima et al (2012), in Gabon by Askew et al (2011), in San Juan basin by Robinson et al (2008), and finally in Oman by Sanchez et al (2012). The theory behind the field observations has not been fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples from applications around the world include Canadian arctic permafrost by Vrielink et al (2008), Lobo field in south Texas by Fontenot (2003), in Brazil by Placido et al (2005 and, Mississippi Canyon by Rosenberg and Gala (2012), in Peruvian Jungle by Beaumont et al (2010), in Saudi Arabia by Chima et al (2012), in Gabon by Askew et al (2011), in San Juan basin by Robinson et al (2008), and finally in Oman by Sanchez et al (2012). The theory behind the field observations has not been fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Larger diameter provides a small pressure drop inside casing but also increases in annular space (Sanchez et al 2012). That means ECD could be higher, which can be alarming, especially in drilling horizontal wells.…”
Section: Hydraulicsmentioning
confidence: 99%
“…Therefore, the team should be focused on providing enough hydraulic energy to clean the bit and prevent the bit balling with high jet velocity, remove cuttings rapidly in order to avoid accumulation inside tight-clearance annulus and flowline, and reduce overall energy consumption (Sanchez et al 2012). …”
Section: Hydraulicsmentioning
confidence: 99%
“…Recent advances in CWD technology Warren et al 2004;Plácido et al 2005;Strickler et al 2005;Warren and Lesso 2005;Sanchez et al 2012) have demonstrated applications of CWD using rotary-steerable assemblies to drill directional wells and, more recently, high-dogleg, high-turn well paths through unstable formations (Avery et al 2009;Chima et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This operation simplifies the process of removing cuttings, seems to assist in mitigating losses, and, most importantly, derisks the well by removing the operations that typically have the highest risks. In the last decade, directional CWD technologies have emerged as a consequence of the significant advantages observed on vertical drilled wells (Plácido et al 2005;Chima et al 2012;Sanchez et al 2012). The use of CWD with a retrievable bottomhole assembly (BHA) ) (CWD Level 3; Fig.…”
Section: Introductionmentioning
confidence: 99%